2019–2020 Florida Citrus Production Guide: Rootstock and Scion Selection - Ute Albrecht; Fernando Alferez; Mongi Zekri (EDIS, 2019)
When preparing for new planting or replanting, an important factor to consider is the choice of rootstock. Choosing the right rootstock and scion combination can result in higher economic returns without any additional cost. Rootstocks affect scion vigor, yield, fruit size and quality, and pest tolerance. However, tree growth, yield, and fruit quality interact strongly with climate, soil type, tree spacing, and other factors, often producing contradictory reports on rootstock performance in different areas. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Ute Albrecht, Fernando Alferez, and Mongi Zekri, and written by the Horticultural Sciences Department, March 2019.